2021
DOI: 10.3390/geosciences11110473
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation EEW Empowered by NDSHA: From Concept to Implementation

Abstract: In this paper, we discuss a possible combination of Earthquake Early Warning (EEW) and Neo-deterministic Seismic Hazard Assessment (NDSHA), and propose a new warning model, EEW2.0. The aim is to provide a differentiated warning alert to various end-users based on the results of seismic hazard assessment evaluation. The implementation of such a system contains three basic steps: (a) classification of “potential to cause hazard” in terms of magnitude; (b) determination of the source areas and building a hazard d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…Earthquake early warning system makes use of the message carried by the P‐wave arrival to issue warnings about the later coming, and potentially destructive, S and surface waves, to field emergency countermeasures, which are scaled to the different objects to be protected (Allen et al, 2009; Allen & Melgar, 2019; Cremen et al, 2022; Kanamori, 2005; Satriano et al, 2011). If the detection network does not cover the seismic source, it has been shown that SHA may help to improve their performance (Cremen & Galasso, 2020; Zhang, Wu et al, 2021). In this paper we focus on the case that the network covers both the seismic source and the target to be protected, and explore how TD‐NDSHA, (see Panza et al, 2022) may help.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Earthquake early warning system makes use of the message carried by the P‐wave arrival to issue warnings about the later coming, and potentially destructive, S and surface waves, to field emergency countermeasures, which are scaled to the different objects to be protected (Allen et al, 2009; Allen & Melgar, 2019; Cremen et al, 2022; Kanamori, 2005; Satriano et al, 2011). If the detection network does not cover the seismic source, it has been shown that SHA may help to improve their performance (Cremen & Galasso, 2020; Zhang, Wu et al, 2021). In this paper we focus on the case that the network covers both the seismic source and the target to be protected, and explore how TD‐NDSHA, (see Panza et al, 2022) may help.…”
Section: Conclusion and Discussionmentioning
confidence: 99%